Genital Crohn’s disease in adolescent boys – A case series - Krishnasamy, Jagannathan (Indian Journal of Child Health, 2019)
Crohn’s disease is an inflammatory bowel disease and involvement of the genital region is rare in this condition. Herein, we are reporting three cases of genital Crohn’s disease in teenage males who were admitted with a chief complaint of swelling in the penis. Recognizing the symptoms and signs, leading to clinical diagnosis and further confirming it by investigations, is a challenge in this condition. Due to limited literature, managing the disease with available evidence becomes crucial. Both medical and surgical treatments play a key role.